DNA Content Variation and SNP Diversity Within a Single Population of Asexual Snails. (27th November 2020) - Million, Kara M; Bhattacharya, Amrita; Dinges, Zoe M; Montgomery, Sarah; Smith, Eries; Lively, Curtis M
Abstract: A growing body of research suggests that many clonal populations maintain genetic diversity even without occasional sexual reproduction. The purpose of our study was to document variation in single-nucleotide polymorphism (SNP) diversity, DNA content, and pathogen susceptibility in clonal lineages of the New Zealand freshwater snail, Potamopyrgus antipodarum . We studied snails that were collected from multiple field sites around a single lake (Lake Alexandrina), as well as isofemale clonal lineages that had been isolated and maintained in the laboratory. We used the kompetitive allele specific PCR (KASP) method to genotype our samples at 46 nuclear SNP sites, and we used flow cytometry to estimate DNA content. We found high levels of SNP diversity, both in our field samples and in our clonal laboratory lines. We also found evidence of high variation in DNA content among clones, even among clones with identical genotypes across all SNP sites. Controlled pathogen exposures of the laboratory populations revealed variation in susceptibility among distinct clonal genotypes, which was independent of DNA content. Taken together, these results show high levels of diversity among asexual snails, especially for DNA content, and they suggest rapid genome evolution in asexuals.